Existence of solutions for some doubly degenerate parabolic equations with natural growth terms. (September 2015) - Zou, Weilin; Wang, Wei
Abstract: This paper deals with a class of doubly degenerate parabolic equations of the type ∂ b ( u ) ∂ t − div ( a ( x, t, u, ∇ u ) ) + F ( x, t, u, ∇ u ) = f, where b is a strictly increasing C 1 -function. Under some suitable hypothesis, we prove that there exists at least a bounded solution to this problem in standard weak sense.